Parental, Peers and Teachers’ Factors as Correlates of Career Choice among Adekunle Ajasin University Undergraduates, Ondo State, Nigeria - Ojewola, Florence O. Ph.D (American Journal of Education and Practice, 2024)
Purpose: The study investigated parental, peers and teachers’ factors as correlates of career choice among Adekunle Ajasin University undergraduates in Ondo State, Nigeria. Materials and Methods: Correlational survey research design was adopted for this study. The population of this study consisted of all Adekunle Ajasin University undergraduates. The sample consisted 296 respondents randomly selected from eight faculties in the University. Simple random sampling technique was used to select six faculties while purposive sampling procedure was used to select fifty respondents from each of the six faculties. A total of 296 respondents were used for the study. A self- designed instrument was used to collect Information on parental, peers and teachers’ factors as correlates of career choice among AAUA students. Four hypotheses were generated and tested at 0.05 level of significance. Regression and Pearson Product Moment Correlation were the statistical tools employed to test the hypotheses in the study. Findings: The findings indicated that there were joint contributions of Peers’, teachers’ and parental influence on the career choice of AAUA students. The result indicated that the students of AAUA were influenced by their peers in their career choice. The influence of parents’ and teachers’ were not prominent in the career choice of AAUA students. Therefore, it is concluded that peers, parental and teachers’ factors collectively influenced the career choice of AAUA students. Implications to Theory, Practice and Policy: It was recommended that parents and teachers need to encourage their children in their choice of career and be careful not to force any career on them. Career guidance and counselling should be made available to the young people so as to assist them in choosing correct and proper career that they have passion for.